Challenges and Opportunities of a Brazilian Network of Universities for the SDG Implementation - Galvão, Thiago Gehre; Menezes, Henrique Zeferino de; Moraes, Leonardo Evangelista; Cabral, Raquel [UNESP]; Maurer, Rafael Lucyk; Pereira, Rudiney Soares; Neiman, Zysman (Springer Nature, 2024)
This chapter delves into the global challenge of implementing the 2030 Agenda, emphasizing the pivotal role of Brazilian Public Universities (BPUs) in realizing this ambitious agenda. Acknowledging the multifaceted challenges in teaching, research, outreach activities, and management, the focus is on how universities, particularly BPUs, can play a crucial role in ensuring access to quality education and generating applied knowledge. This chapter focus on the potential for these universities to become key players by forming collaborative networks to address the challenges of localizing the 2030 Agenda and Sustainable Development Goals (SDGs). As integral components of their local communities, public universities contribute significantly to local economies and act as knowledge hubs producers. The core objective of this chapter is to critically assess the prospects for creating a Brazilian university network committed to integrating SDGs into core activities, emphasizing the synergistic capacity of SDG 4 and the transformative power of education. The narrative underscores the fundamental role of BPUs in addressing social inequalities and promoting inclusive education, positioning them as crucial for the successful territorialization of the 2030 Agenda. This chapter concludes by highlighting the opportunities for networking between universities and various stakeholders, presenting outreach activities as a promising path for BPUs to assume a leading role in implementing the 2030 Agenda and the SDGs.
Keywords: 2030 Agenda; Sustainable Development Goals (SDGs); Territorialization